Eksplorasi Tindak Tutur dalam Novel Paya Nie Karya Ida Fitri: Kajian Pragmatik - Amir, Johar; Ridwan, Ridwan; Ratih, Ratih (Gurindam: Jurnal Bahasa dan Sastra, 2025)
This study aims to examine the forms of speech acts in Ida Fitri's novel Paya Nie using a pragmatic approach. This study focuses on three types of speech acts: locutionary, illocutionary, and perlocutionary. The method used is qualitative descriptive with data collection techniques through listening and note-taking on quotations in the novel. The results of the study indicate that Ida Fitri's novel Paya Nie contains various forms of speech acts that reflect the dynamics of interaction between characters in the social and cultural context of Acehnese society, which is experiencing conflict. Locutionary acts are found in the form of conveying information, illocutionary acts in the form of expressing feelings and invitations, and perlocutionary acts in the form of emotional effects and changes in the attitude of the addressee.